Aplicação do processo de liofilização na obtenção de cajá em pó: avaliação das características físicas, físico-químicas e higroscópicas - Oliveira, Gleison Silva (2012)
The yellow mombin due to its distinctive flavor and pleasant, is a fruit highly appreciated and consumed in various regions of the country. But by presenting a high perishability, it becomes necessary to use processing techniques to extend its availability for consumption throughout the year. Dehydration by freeze-drying has the advantage of an excellent retention of nutritional and sensory characteristics of fresh fruit. To increase retention and to prevent agglomeration of the powder, for example, can be made the use of adjuvants drying such as maltodextrin. In this context, the work aimed at the implementation of the lyophilization process to obtain the pulp of yellow mombin powder, physical characterization and physicochemical pulp and powder yellow mombin, tracking stability during storage and hygroscopic behavior of the tests. With the tests of the experimental design was chosen to test lower humidity, with 17% maltodextrin and 24 hours of freeze drying. The pulp presented characteristics similar to reported by literature, and a concentration of constituents occurred with the pulp dehydration. As for storage, the test control (dried whole) had a useful life of 60 days, unlike the test containing maltodextrin that showed good characteristics throughout the period analyzed. In addition, maltodextrin exerted protective function, preventing further loss of chemical constituents and physical reactions to the product, such as lower rate of increase of hygroscopicity, moisture and water activity. The adsorption isotherms were the characteristics of type III. The mathematical models of BET, GAB and Oswin were the best fit to experimental data of moisture sorption for the full hog plum powder, and powder of hog plum pulp with maltodextrin, the Henderson model was the best fit to experimental points of work.